Answer:
x = 2/5, y= -22/5
Explanation:
4x−y=6;3x−2y=10
Step: Solve4x−y=6for y:
4x−y+−4x=6+−4x(Add -4x to both sides)
−y=−4x+6
-y/-1 = -4x +6 over -1 (Divide both sides by -1)
y=4x−6
Step: Substitute4x−6for y in 3x−2y=10:
3x−2y=10
3x−2(4x−6)=10
−5x+12=10(Simplify both sides of the equation)
−5x+12+−12=10+−12(Add -12 to both sides)
−5x=−2
-5x/-5 = -2/5 (Divide both sides by -5)
x= 2 /5
Step: Substitute 2/ 5 for x in y=4x−6:
y=4x−6
y=4 ( 2/ 5 ) −6
y= −22 /5
(Simplify both sides of the equation)
x = 2/5, y= -22/5